Association between PPP2CA polymorphisms and clinical features in southwest Chinese systemic lupus erythematosus patients. Issue 27 (July 2018) - Zhang, Junlong; Meng, Yanming; Wu, Hengxu; Wu, Yongkang; Yang, Bin; Wang, Lanlan
Abstract : Abstract: Increasing evidence supports the involvement of a catalytic subunit (PP2Ac) of protein phosphatase 2A (PP2A) in the mechanisms of systemic lupus erythematosus (SLE). This study was conducted to explore the association single nucleotide polymorphisms (SNPs) of PPP2CA with SLE susceptibility, serum cytokines levels, and clinical features in a Chinese Han population. A case–control association study was carried out in 1509 Chinese Han subjects (730 SLE patients and 779 healthy individuals). Genotyping for genetic variants of PPP2CA (rs10491322 and rs7704116) was performed using a polymerase chain reaction-high resolution melting (PCR-HRM) assay. In the cohort of SLE patients, we observed that rs10491322 and rs7704116 were positively increased SLE susceptibility (OR = 1.61, 95% CI = 1.13–2.31, P  = .009; OR = 1.59, 95% CI = 1.17-2.15, P  = .003, respectively). Interestingly, the AG genotype of rs10491322 carriers presented higher IL-6 ( P  < .001) and IL-17 ( P  < .001) than those with AA genotype carriers. Specifically, carriage of the rs10491322 G* allele led to a higher prevalence of arthritis in SLE patients ( P  = .01). This study demonstrated an association of PPP2CA (rs10491322 and rs7704116) with SLE susceptibility in a Chinese Han population. Furthermore, the minor allele of PPP2CA rs10491322 as a risk factor was correlated with immunologic disorders for SLE.